2018
DOI: 10.1002/jsfa.9327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agronomic practices on grape aroma composition: a review

Abstract: Aroma compounds are secondary metabolites that play a key role in grape quality for enological purposes. Terpenes, C -norisoprenoids, phenols, and non-terpenic alcohols are the most important aroma compounds in grapes and they can be found as free volatiles or glycoconjugated (bound) molecules. The non-volatile glycosylated group is the largest, and it is present in all varieties of Vitis vinifera (L.), the most widely used species for wine production. These aroma precursors represent the reserve of aroma mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 117 publications
(250 reference statements)
4
80
1
1
Order By: Relevance
“…Fifty grape sampling time points spreading to 86 days were established and normalized using the cumulative growing degree days parameter. The results confirmed that vine-shoot extract treatment had a positive impact on the accumulation of glycosylated compounds [45], especially aglycones such as alcohols, terpenes, and C13-norisoprenoids, with a higher impact when the treatment was applied at grape ripening stage.…”
Section: Effect Of Application Of Exogenous Stimulants Of Fruit Metabsupporting
confidence: 64%
“…Fifty grape sampling time points spreading to 86 days were established and normalized using the cumulative growing degree days parameter. The results confirmed that vine-shoot extract treatment had a positive impact on the accumulation of glycosylated compounds [45], especially aglycones such as alcohols, terpenes, and C13-norisoprenoids, with a higher impact when the treatment was applied at grape ripening stage.…”
Section: Effect Of Application Of Exogenous Stimulants Of Fruit Metabsupporting
confidence: 64%
“…Introduction Fruit composition, though partly determined by genotype and uncontrolled environmental conditions, can be managed to some extent through the optimisation of agricultural practices, such as vineyard floor management, fertilisation, canopy management and crop thinning, before and during fruit development (Masclaux-Daubresse et al 2010;Sweetman et al 2014;Alem et al 2019). The effect of crop load on C assimilation and partitioning has been extensively studied (Chaves 1984;Morinaga et al 2003;Dai et al 2010).…”
Section: Impact Of Crop Load On Nitrogen Uptake and Reserve Mobilisatmentioning
confidence: 99%
“…The effects of water deficit on flavor and aroma potential are less evident than for phenolic compounds derived from the phenylpropanoid pathway. Depending on the type of aroma precursor, water availability can have various effects as reviewed by Alem et al (2019). Moreover, as for phenylpropanoids it is often difficult to deduce physiological effects of water deficit because most papers present results on a concentration basis without berry weight or volume data, thus concentration effects due to berry volume changes preclude a physiological interpretation.…”
Section: Impact Of Water Deficit On Berry Physiology and Compositionmentioning
confidence: 99%